Cultural osteology. 2do. Book. Cephalic Practices: a) Intentional Deformations of the Head. b) Paleopathology. - Weiss, Pedro (1961)
We have already defined at another time (79) what we mean by Cultural Osteology. In short, it is the study of disorders of the bones either intentional causes (deformations, trepanation, cauterization, etc..) environmental (stressantes or nutritional changes and pathological factors) disease. tumors, infections, etc., considered as a feature, combining them with the time, geographic region and tracking potential partnerships with other characters.